Precise Incubation Period for the Agrobacterium- mediated Transformation Efficiency in Potato (Solanum tuberosum L.) cvs. Cardinal and Atlas (Plant Tissue Culture and Biotechnology, 2010)
Precise incubation period facilitates significant response to Agrobacterium- mediated genetic transformation of potato (Solanum tuberosum L.) cvs. Atlas and Cardinal. The protocol yielded an average transformation rate of 58.4% for internodal explants compared to 38% for leaf explants in Atlas while 47.6% for intenodal explants as against 7.6% for leaf explants in Cardinal. Highest survival rate and transient GUS activity were shown by Atlas and Cardinal at 45 min of incubation with Agrobacterium. The plants were analyzed histochemically for GUS activity in their leaves and internodes. All these analysis indicated that each independently selected and regenerated plants of Atlas and Cardinal were GUS positive and transient.  Key words:  Transformation, Incubation period, Potato cultivars D.O.I. 10.3329/ptcb.v19i2.5440 Plant Tissue Cult. & Biotech. 19(2): 227-235, 2009 (December)